Role of non metallic Nano additive in the behavior of a diesel engine fueled with blends of Waste plastic oil. Issue 1 (April 2021) - Sachuthananthan, B.; Vinoth, R.; Reddy, D. Raghurami; Reddy, K. Harshavardhan
Abstract: This study analyze about the efficiency improvement and emission reduction of a 4 stroke mono cylinder diesel engine fueled by 20 % by volume mixture of Waste Plastic Oil (WPO) blended with 80 % diesel and different proportion of non metallic nano additive. WPO was extracted through the pyrolysis process using plastic wastes collected from near by areas. Nano additives made from rice husk was blended @ 25ppm, 50ppm, 75ppm and 100ppm. The fuel mixture was tested for its stability and later used in diesel engine for performance, emission and combustion characters. Result indicate that for W20 mixture without additives revealed 3.5 % drop in brake thermal efficiency (BTE) and Brake specific fuel consumption (BSFC) increased by 5.7 % at a full load condition when equated with diesel. With the blending of Non metallic Nano additives (NA), the BTE increased by 2.6 % and fuel consumption reduces by 3.1% for the W20NA75 blend when compared to other blends. Emissions parameters like hydrocarbon (HC), carbonmonoxide (CO) and smoke opacity reduced by 15.3%, 7%, and 20.4% respectively with rise in oxides of nitrogen (NOx) emission by 14.1% when equated to diesel at maximum load condition. It can be concluded that 75ppm rice husk nanoparticles added with W20 blend helped to rise the efficiency characters and reduces engine out pollutants of a CI engine.